2019
DOI: 10.1080/07420528.2019.1629449
|View full text |Cite
|
Sign up to set email alerts
|

Sleep architecture is related to birth season in 1-month-old infants

Abstract: Individual variation in sleep quality, quantity, and architecture is pronounced in small infants. Reasons for this remain largely unclear, even though environmental and genetic factors have been suggested to play a role. In order to study the effect of birth seasons on infant sleep architecture, 85 healthy 1-month-old infants underwent an overnight polysomnography (PSG). The PSGs were conducted in 2011-2013. The cohort was divided into four subgroups according to the amount of seasonal light at the time of bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In our previous study, we found a greater abundance of R/REM sleep in 1-month-old infants born during the summertime than those infants born in the winter (Kärki et al 2019). In our current study, when the children are approximately 7 months older, however, we did not find any REM sleep differences between the birth season groups.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In our previous study, we found a greater abundance of R/REM sleep in 1-month-old infants born during the summertime than those infants born in the winter (Kärki et al 2019). In our current study, when the children are approximately 7 months older, however, we did not find any REM sleep differences between the birth season groups.…”
Section: Discussionmentioning
confidence: 72%
“…In our previous PSG study, we found that 1-month-old infants born in the summer in Finland present more R sleep than infants born in winter (Kärki et al 2019). In addition, infants presented less T sleep (transient, immature sleep stage) during the summer when compared to the winter, and shorter nighttime sleep when compared to the autumn.…”
Section: Introductionmentioning
confidence: 79%
“…More research is needed to investigate whether or how different aspects of parental behavior influence infant sleep across the four quarters of the first year of life. A recent Finnish study documented that natural and artificial light have an impact on sleep architecture in 1 month old infants [ 90 ]. Climatic variations may also have an impact on infant sleep development; however, more research is needed to clarify the mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…& duration of daytime naps. PSG: %REM, %N1, %N2, %N3, %NREM, Wakefulness, TST, Sum of awaking & arousal index, %SE, WASO, Sleep onset latency, REM onset latency (Karki et al, 2019 ) Sleep development 85 (43:42) 1 month old Overnight home polysomnography %REM, %NREM, Wakefulness, TST, Sum of awaking and arousal index, %SE, WASO, No. of times awake (Kocevska et al, 2018 ) Sleep patterns 6,808 2 years old Questionnaires Bedtime, Wake time, Amount of daytime sleep, Total sleep duration (Korotchikova et al, 2016 ) Sleep development 80 (42:38) Within 36 hs after birth Continuous Video-EEG AS, QS, IS, Wakefulness, Sleep–wake cycle (Korte et al, 2004 ) Sleep development 57 (32:25) Birth—6 days old Actigraph Daytime sleep, night-time sleep, 24 h sleep (Ktonas et al, 1995 ) Sleep development 28 2–6 weeks = 10, 7–14 weeks = 10, 16–48 weeks = 8 2–6, 7–14, 16–48 weeks Whole night polysomnography Longest phase of QS, Mean, SD, and range of the longest period of QS (Lampl & Johnson, 2011 ) Sleep and growth 23 (9:14) 4–17 months old Sleep records No.…”
Section: Resultsmentioning
confidence: 99%
“…Summer born infants were reported to have shorter TST (Karki et al, 2019 ; Kärki et al, 2020 ). Parental presence at bedtime, frequency of night-awakenings, and less TST at one month of age predicted poor sleep at six and twelve months (Henderson et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%